Violencia domestica y trastorno por estrés postraumático en un niño de 8 años - Soto Quinto, Enma Filomena (2020)
People with PTSD work hard to escape and avoid what they fear. When they are forced to face each other, they do it with a lot of male, they are determined by the direct and indirect assistance of domestic violence and by various aspects of acting and interaction in social situations, the components of fear, avoidance becoming important. Different evolutionary, family, environmental, evolutionary, temperamental, neurobiological, genetic, biological, psychological and sociocultural factors are associated with this disorder, reflecting its great complexity. The acquisition of fear, anxiety and disruptive behaviors are caused by experiencing a traumatic situation or witnessing a traumatic experience of another person. The objective of this theoretical study is to show a description of the way in which these factors are associated with post-traumatic stress disorder, as well as the main studies related to it. What will empower essential tools for the comprehensive approach and diagnosis of the disorder in references.